2022
DOI: 10.1055/s-0042-1755329
|View full text |Cite
|
Sign up to set email alerts
|

Protein Tyrosine Phosphatase 1B Deficiency in Vascular Smooth Muscle Cells Promotes Perivascular Fibrosis following Arterial Injury

Abstract: Background Smooth muscle cell (SMC) phenotype switching plays a central role during vascular remodeling. Growth factor receptors are negatively regulated by protein tyrosine phosphatases (PTPs), including its prototype PTP1B. Here, we examine how reduction of PTP1B in SMCs affects the vascular remodeling response to injury. Methods Mice with inducible PTP1B deletion in SMCs (SMC.PTP1B-KO) were generated by crossing mice expressing Cre.ERT2 recombinase under the Myh11 promoter with PTP1Bflox/flox mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…S2B ). MC3 was marked by MYH11 and actin alpha 2, smooth muscle ( ACTA2) and identified as myofibroblasts 23 (Fig. S2B, C ).…”
Section: Resultsmentioning
confidence: 99%
“…S2B ). MC3 was marked by MYH11 and actin alpha 2, smooth muscle ( ACTA2) and identified as myofibroblasts 23 (Fig. S2B, C ).…”
Section: Resultsmentioning
confidence: 99%
“…Berdnikovs et al furthermore demonstrated that PTP1B was involved in inflammation as inducible endothelial cell-specific deletion of PTP1B showed a significant increase in accumulation of eosinophils bound to the luminal surface of the endothelium in the lung vasculature and had a decrease in leukocyte recruitment into the lung tissue during ovalbumin-induced allergic lung inflammation[34]. Furthermore, in response to arterial injury, vascular smooth muscle cells deficient for PTPN1 promoted perivascular fibrosis [17]. During respiratory syncytial viral-induced exacerbation of chronic obstructive pulmonary disease, PTPN1 deficiency was shown to promote disease symptoms partly through enhancing S100A9 levels, a damage-associated molecular pattern molecule [35].…”
Section: Discussionmentioning
confidence: 99%
“…Adenoviral mediated overexpression of dominant negative PTPN1 increased neointima formation in injured rat carotid arteries [16]. Furthermore, following vascular injury, mice deficient to PTPN1 in SMCs developed perivascular fibrosis in carotid arteries[17]. Using hypoxic PASMCs and hypoxia-induced PH mouse models, Freyhaus et al ., demonstrated that hypoxia promoted PDGFRB pathway signaling through inhibiting PTPs, such as SHP-2, TC-PTP, DEP-1, and PTPN1 [18].…”
Section: Introductionmentioning
confidence: 99%
“…S2B). MC3 was marked by MYH11 and actin alpha 2, smooth muscle (ACTA2) and identified as myofibroblasts 22 (Fig. S2B, C).…”
Section: Adam12 Expression Defines Multipotent Profibrogenic Mesenchy...mentioning
confidence: 99%